MEMS Test Bench and its Uncertainty Analysis for Evaluation of MEMS Mirrors. Issue 15 (2019) - Yoo, Han Woong; Brunner, David; Thurner, Thomas; Schitter, Georg
Abstract: This paper proposes a MEMS test bench to ensure highly accurate and precise angle measurements for evaluation of multiple MEMS mirrors and analyzes its measurement uncertainty. The MEMS test bench includes a position sensitive detector (PSD) with a motorized stage to convert the beam displacement on the PSD to a mirror angle measurement by a dedicated calibration procedure. Uncertainties in the angle measurement of the MEMS mirrors are analyzed considering the optical alignment, the characterization of the PSD, and the calibration data. By the proposed uncertainty analysis, the accuracy of the developed MEMS test bench shows up to 0.026° at the mirror angle of 15°.